THE INFLUENCE OF SOCIAL MEDIA MARKETING ON PURCHASING DECISIONS AT NITO SUPERIOR SEED SHOPS IN NORTH TORAJA DISTRICT - Mangoki, Lidia; Batara Marewa, Jens; Kurniasari Wibisono, Lisa (JURNAL EKBIS, 2024)
The Influence of Social Media Marketing on Purchasing Decisions at the Nito Superior Seed Shop in North Toraja Regency. The purpose of this research is to determine the influence of social media marketing on purchasing decisions. This research uses a quantitative approach with simple linear regression analysis. The sample in this study was taken from buyers of Nito Superior Seeds in North Toraja Regency. Data collection was carried out by distributing questionnaires. In this research, the data source used is primary data. The research instrument used in this study used a non-probability sampling method. The results showed that data using statistical calculations via the Statistical Package for the Social Science (SPSS) version 25 application obtained a significance value of 0.007 < 0.05 and at value of 2.875 > t table value 1, 01954 which can be concluded that Social Media Marketing has a positive and significant influence on the decision to purchase superior seeds in North Toraja Regency.